FACTORS MOTIVATING STUDENTS’ SPEAKING IN ENGLISH DRAMA CLASS - Natalia, Emilia; Marbun, Rismaya; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
The purpose of this research is to describe the factors motivating students’ speaking in English drama class on the sixth semester students of English Education Study Program Tanjungpura University. Factors of motivation can influence students’ motivation to increase their ability in speaking.This research involve 28 students of English drama class. The researcher applied descriptive method in qualitative approach.The data of this research were obtained by interview the students and transcribe the result of the interview. There are some factors of motivation for this research. They are teachers’ factor, teachers’ love factor, teachers’ care factor, teachers’ interaction factor, teacher sense of humor factor, classroom athmosphere factor, self-development factor, gain respected factor, competition factor, self-confident factor, possible – selves factor, parents’ factor. Keywords : factor motivating, speaking, drama. Abstrak: Tujuan dari penelitian ini yaitu untuk mendeskripsikan faktor-faktor yang memotivasi siswa-siswa berbicara dalam bahasa Inggris di kelas drama pada siswa-siswa semester VI Pendidikan Program Bahasa Inggris di Universitas Tanjungpura. Faktor-faktor motivasi dapat mendorong siswa untuk meningkatkan kemampuan dalam berbicara. Penelitian ini melibatkan 28 siswa kelas drama bahasa Inggris. Peneliti mengaplikasikan metode deskripif dalam pendekatan kualitatif. Data dari penelitian ini diperoleh dari mewawancarai siswa dan menulis hasil dari wawancara. Ada beberapa faktor-faktor motivasi dalam penelitian ini. Faktor-faktor tersebut yaitu faktor guru, faktor cinta dari guru, faktor kepedulian guru, faktor interaksi dari guru, faktor humor dari guru, faktor suasana kelas, faktor pengembangan diri, faktor memperoleh hormat, faktor bersaing, faktor kepercayan diri, faktor kemungkinan-diri, faktor dari orang tua. Kata kunci: faktor-faktor pemotivasian, Berbicara, Drama.